Molecular Determinants Responsible for Sedative and Non-sedative Properties of Histamine H1-Receptor Antagonists - Yoshihiro Uesawa; Shigeru Hishinuma; Masaru Shoji (Elsevier, 2014)
There is argument whether non-sedative properties of histamine H1-receptor antagonists (antihistamines) are determined by their active extrusions from the brain via P-glycoprotein or their restricted penetration through the blood-brain barrier. We have reported that sedative and non-sedative antihistamines can be well discriminated by measuring changes in their binding to H1 receptors upon receptor internalization in intact cells, which depends on their membrane-penetrating ability. In this study, molecular determinants responsible for sedative and non-sedative properties of antihistamines were evaluated by quantitative structure-activity relationship (QSAR) analyses. Multiple regression analyses were applied to construct a QSAR model, taking internalization-mediated changes in the binding of antihistamines as objective variables and their structural descriptors as explanatory variables. The multiple regression model was successfully constructed with two explanatory variables, i.e., lipophilicity of the compounds at physiological pH (logD) and mean information content on the distance degree equality (IDDE) (r2 = 0.753). The constructed model discriminated between sedative and non-sedative antihistamines with 94% accuracy for external validation. These results suggest that logD and IDDE concerning lipophilicity and molecular shapes of compounds, respectively, predominantly determine the membrane-penetrating ability of antihistamines for their side effects on the central nervous system. Keywords:: histamine H1 receptor, antihistamine, sedation, membrane penetration, P-glycoprotein